2020
DOI: 10.1002/ecs2.3088
|View full text |Cite
|
Sign up to set email alerts
|

Pika burrow and zokor mound density and their relationship with grazing management and sheep production in alpine meadow

Abstract: Plateau pikas (Ochotona curzoniae) and plateau zokors (Myospalax baileyi) occur naturally in the alpine meadow of the Qinghai–Tibet Plateau (QTP). Their feeding and burrowing activities affect plant composition and soil properties (e.g., soil carbon accumulation and soil nitrogen cycling), but research to study the complex interactions between small mammals, livestock, and habitat is currently lacking. We conducted a sheep grazing trial to determine the effect of grazing management on pika burrow and zokor mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…The results of this study showed a density of 5500 pika burrows/ha in degraded alpine shrub meadow, whereas surveys conducted in the western part of the southern Qilian Mountains have shown that the average number of pika burrows in normal grassland is 300–800 burrows/ha (Qin, Sun, et al, 2020; Qin et al, 2019; Yi et al, 2016). In contrast, studies of degraded alpine grassland in the hinterland of QTP found the average number of pika burrows to be 2700–4775 burrows/ha (Liu et al, 2017; Tian et al, 2019; Wang et al, 2020; Wei et al, 2013), and in the degraded grasslands of the eastern QTP, the density of pika burrows can even reach 7066 burrows ha −1 (Zhang et al, 2021), which is close to our results. The density of pika burrows has been proven to be significantly correlated with the coverage of vegetation and bare soil (Tang et al, 2019; Zhang et al, 2021), and it is also a valid indicator to estimate the population size of pika in the plateau.…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study showed a density of 5500 pika burrows/ha in degraded alpine shrub meadow, whereas surveys conducted in the western part of the southern Qilian Mountains have shown that the average number of pika burrows in normal grassland is 300–800 burrows/ha (Qin, Sun, et al, 2020; Qin et al, 2019; Yi et al, 2016). In contrast, studies of degraded alpine grassland in the hinterland of QTP found the average number of pika burrows to be 2700–4775 burrows/ha (Liu et al, 2017; Tian et al, 2019; Wang et al, 2020; Wei et al, 2013), and in the degraded grasslands of the eastern QTP, the density of pika burrows can even reach 7066 burrows ha −1 (Zhang et al, 2021), which is close to our results. The density of pika burrows has been proven to be significantly correlated with the coverage of vegetation and bare soil (Tang et al, 2019; Zhang et al, 2021), and it is also a valid indicator to estimate the population size of pika in the plateau.…”
Section: Discussionmentioning
confidence: 98%
“…High ecosystem multifunctionality may show a higher sensitivity response to STC, SM, PD, and AGB ( Figure 6B ). Previous studies had used observational data to indicated that ecosystem functions differ in their sensitivity to grazing pressure (Ren et al, 2018 ) and restoration practices (Wang et al, 2020b ). In this case, the lower ecosystem coupling and multifunctionality in Stage 4 induced by grazing may be caused by several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, these considerations may be not significant in NTXJ because the grazing duration on alpine grassland is short, lasting only one to two months, and is often concentrated in summer [50]. However, compared with NTXJ, throughout other alpine meadows, or grassland areas in the world [51][52][53], longer grazing durations may indeed have a more significant impact on the population density of rodents. In addition, in alpine meadows, small rodents such as pika may spend the winter by eating yak feces [54], so the population density and grazing intensity may also show a positive correlation.…”
Section: Other Potential Impacts Of Grazing On Rhdmentioning
confidence: 99%